Education Law for the Future: Summary of the hybrid international expert seminar at the Pázmány Péter Catholic University - Meix Cereceda , Pablo; Gerencsér, Balázs Szabolcs; Balla, Boróka Luca (Pázmány Law Review, 2023)
This paper summarises the outcomes of an international scientific expert seminar titled Education Law for the Future held at the Faculty of Law and Political Sciences of the Pázmány Péter Catholic University in cooperation with the European Association for Education Law and Policy. Professors, professionals and experts were invited world-wide to share their opinion and research results. The expert seminar underlined the need for the rephrasing of international law related to the right to education as well as the importance of rethinking the relation between hard and soft law in domestic legislation.